ANALISIS NILAI MORAL PADA PANTUN ADAT PERKAWINAN MASYARAKAT MELAYU KABUPATEN KARIMUN PROVINSI KEPULAUAN RIAU - Erni Erni; Supriyadi Supriyadi; Jusliani Jusliani (UIR Press, 2014)
Pantun for Malay community in Kabupaten Karimun is a popular literary, for this reason the writers are interested to raise this problem by assigning the title